Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1210/en.2009-0390
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin D Is the Primary Protease for the Generation of Adenohypophyseal Vasoinhibins: Cleavage Occurs within the Prolactin Secretory Granules

Abstract: Vasoinhibins are a family of N-terminal prolactin (PRL) fragments that inhibit blood vessel growth, dilation, permeability, and survival. The aspartyl endoprotease cathepsin D is active at acidic pH and can cleave rat PRL to generate vasoinhibins. We investigated whether and where vasoinhibins could be generated by cathepsin D in the adenohypophysis of rats and mice and whether their production could be gender dependent. Vasoinhibins were detected in primary cultures of rat adenohypophyseal cells by Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 51 publications
2
27
0
1
Order By: Relevance
“…Accordingly, vasoinhibins can be generated by cathepsin D during the pituitary PRL secretory process and thus, subjected to regulated release. Along this line, estradiol increases the synthesis and activity of cathepsin D [24], and the production of anterior pituitary vasoinhibins is higher in females [23], increases at proestrus with respect to diestrus, and estrogens stimulate their release [25].…”
Section: Generation Of Endogenous Vasoinhibinsmentioning
confidence: 96%
See 1 more Smart Citation
“…Accordingly, vasoinhibins can be generated by cathepsin D during the pituitary PRL secretory process and thus, subjected to regulated release. Along this line, estradiol increases the synthesis and activity of cathepsin D [24], and the production of anterior pituitary vasoinhibins is higher in females [23], increases at proestrus with respect to diestrus, and estrogens stimulate their release [25].…”
Section: Generation Of Endogenous Vasoinhibinsmentioning
confidence: 96%
“…Cathepsin D is catalytically active at acidic pH (pH < 5.5), and recent findings showed that it is the main vasoinhibin-generating enzyme in anterior pituitary lactotrophs [23]. Cathepsin D is located in PRL secretory granules, which are acidic, and cathepsin-D null mice are devoid of vasoinhibins in the anterior pituitary gland [23].…”
Section: Generation Of Endogenous Vasoinhibinsmentioning
confidence: 99%
“…Under normal conditions, a pericellular acidic pH can be produced by the activity of the Na C /H C exchanger and H C /ATPase (Piwnica et al 2006). In rat anterior pituitary cells, Cath D was present in PRL secretory granules and has been proposed to be the main protease involved in 16 kDa PRL production (Cruz-Soto et al 2009). Our present data show the cleavage of mPRL to N-terminal mPRL fragment in media from cultures of MG fragments, but this reaction did not occur in the absence of MG fragments, supporting the hypothesis that mature Cath D secreted from MECs produces the N-terminal mPRL fragment in the extracellular milieu.…”
Section: Mrmentioning
confidence: 99%
“…Cleavage of rat PRL by Cath D produces a single 16 kDa vasoinhibin (amino acids (aa) 1-145), whereas from human PRL, this enzyme generates vasoinhibins 1-132 (15 kDa), , and 1-150 (17.2 kDa). All these cleavages of full-length native PRL by proteases generated N-terminal 14-18 kDa fragments (Cruz-Soto et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Des formes clivées, PRL 14 kDa et 16K, ont été détectées dans les granules sécrétoires de l'adénohypophyse [6]. Chez l'homme et plusieurs mammifères, les ARNm et la PRL elle-même sont aussi exprimés dans la glande mammaire et dans le lait, où coexistent diverses formes moléculaires de la PRL (14,18,20,23,25 kDa) [7,8].…”
Section: Prl 23 Kda Et 16k Dans Les Tissus De Mammifèresunclassified